Optimization of Magnetorheological Elastomer composition and ferrous particle size for enhanced sound absorption performance - Mohd Razali, Ahmad Nabil; Hudha, Khisbullah; Abd Kadir, Zulkiffli; Mohamed Ishak, Saiddi Ali Firdaus; Ruslan, Noor Amira Ilyanie; Amer, Noor Hafizah (UiTM Press, 2025)
Nowadays, Magnetorheological Elastomers (MREs) are widely used in real applications such as vibration absorbers, isolators, magnetoresistors, and electromagnetic wave absorbers. The MR effect refers to the modulus feedback generated by MREs. When exposed to a magnetic field, the mechanical and viscoelastic properties of MREs can be reversibly altered. MREs are composite materials consisting of magnetizable particles embedded within a solid elastomer matrix. Their behavior is influenced by factors such as the type and size of the dispersed magnetic particles, the elastomer matrix composition, and the presence of non-magnetic fillers like plasticizers, carbon black, and crosslinking agents. This research investigates how the sound absorption capability of MREs is affected by their composition and the size of ferrous particles. The primary objective is to determine the optimal MRE composition for sound absorption and to analyze the impact of varying ferrous particle sizes on this property. MREs are synthesized using carbonyl iron particles, a hardener, and RTV silicone rubber. Since the performance of MREs actual applications is significantly influenced by the size of ferrous particles, experimental evaluations are conducted to determine the optimal parameters for MRE composition. Finally, the fabricated MREs are tested in a laboratory setting to assess their sound absorption capabilities. Based on the experimental tests, the optimal amounts of carbonyl iron particles, RTV silicone rubber, and hardener are 15 g, 9 g, and 0.45 g, respectively.